Miniaturized Bandpass Filter Using a Meandered Stepped-Impedance Resonator with a Meandered-Line Stub-Load on a GaAs Substrate - Z. Chuluunbaatar; C. Wang; N. Y. Kim (The Scientific World Journal)
This paper reports a compact bandpass filter with improved skirt selectivity using integrated passive device fabrication technology on a GaAs substrate. The structure of the filter consists of electromagnetically coupled meandered-line symmetric stepped-impedance resonators. The strength of the coupling between the resonators is enhanced by using a meandered-line stub-load inside the resonators to improve the selectivity and miniaturize the size of the filter. In addition, the center frequency of the filter can be flexibly controlled by varying degrees of the capacitive coupling between resonator and stub-load. To verify the proposed concept, a protocol bandpass filter with center frequency of 6.53 GHz was designed, fabricated, and measured, with a return loss and insertion loss of 39.1 dB and 1.63 dB.